OPTIMIZATION OF WITNESS AND VICTIM PROTECTION WITHIN THE FRAMEWORK OF ACCESS TO JUSTICE: A COMPARATIVE STUDY OF THE PROGRESSIVENESS OF INDONESIAN AND THAI LAW - Tarigan, Gema Akbar; Rahmi , Atikah (Pena Cendekia Insani, 2026)
This study aims to analyze and compare the witness and victim protection systems in the criminal procedural law of Indonesia and Thailand. The main focus of this research is to understand how both countries regulate the protection of witnesses and victims and identify significant differences in their legal frameworks and implementation practices. In Indonesia, witness and victim protection is regulated by Law No. 13 of 2006, later amended by Law No. 31 of 2014, which provides rights to physical and psychological protection, legal assistance, and restitution. Despite having a clear legal framework, the implementation of protection in Indonesia faces significant challenges, such as limited resources for the Witness and Victim Protection Agency (LPSK), insufficient coordination among law enforcement agencies, and low public awareness of the rights of witnesses and victims. In contrast, Thailand, through the Witness Protection Act B.E. 2546, offers more participatory rights to victims by allowing them to engage in private prosecution, enabling victims to play an active role in the prosecution process. However, Thailand also faces similar challenges related to inter-agency coordination and resource limitations. This study concludes that although both countries have strong legal frameworks, witness and victim protection on the ground remains limited by practical and institutional factors. Recommendations for both countries include enhancing institutional capacity, improving inter-agency coordination, and expanding victim participation in the legal process to improve the effectiveness of witness and victim protection.